THE DEVELOPMENT OF CONTEMPORARY INDONESIAN INTERPRETATION: RESEARCH EPISTEMOLOGICAL TRENDS 2020–2025 - Bahrudin, Moh.; Mukti, Anwar; Cahyono, Agung Mandiro; Hakim, M. Luqman; Fathoni, Ahmad Nur; Karim, Muhammad Burhanudin Nur (West Science Islamic Studies, 2024)
The development of Qur’anic exegesis in Indonesia between 2020 and 2025 demonstrates significant epistemological transformations driven by the growing need to interpret the Qur’an in ways that are contextual, interdisciplinary, and responsive to contemporary social dynamics. This study aims to map four major epistemological trends shaping the new direction of contemporary Indonesian tafsīr: the integrative paradox between classical tradition and modern methodology; the reformulation of feminist exegesis through the Qirā’ah Mubādalah approach; the expanding dialogue between the Qur’anic text and modern science, which shifts interpretation from literalism toward scientific contextualism; and the emergence of digital epistemology, which transforms the production, dissemination, and validation of tafsīr. Employing a qualitative-descriptive method grounded in Gadamerian hermeneutics and discourse analysis, this research examines exegetical works, academic studies, institutional documents, and digital tafsīr content produced between 2020 and 2025. The findings reveal that the epistemology of Indonesian tafsīr is moving toward a synthetic model that reaffirms textual authority while opening space for dialogue with contemporary realities. The integration of hermeneutics, maqāṣid al-sharī‘ah, multi-criteria validation theories, and digital technologies has generated an interpretive paradigm that is more reflective, adaptive, and oriented toward public welfare. This study concludes that such epistemological transformations not only enrich the methodology of Qur’anic exegesis but also offer new directions for the future development of Qur’anic studies in the modern era.